Parental School Involvement on Physical Activity and Screen Time Among Middle and High School Students - Joseph Greer; Kiran Thapa; Jessica McNulty; Janani Thapa (Georgia Southern University, 2021)
Background: High levels of sedentary activity and low levels of physical activity have led to an increase in childhood obesity. A reduction of sedentary behavior and the promotion of an active lifestyle positively impacts weight status of children. A child may modify their behavior through direct interventions from their parents, such as enforcement of rules or guided activities, or through broad interventions, by expressing their values and modeling behavior. Current research does not establish if broad or specific parental involvement has a greater effect on healthy behavior. Our group sought to support existing evidence that parental involvement directly impacts behavior that reduces the likelihood of childhood obesity and determines if broad or specific parental involvement had a greater impact on healthy behavior. Methods: The study population included all children grades 6-12 who completed the Georgia Student Health Survey 2.0. Survey questions from 674,354 students in Georgia were used for the analysis. Exploratory factor analysis (EFA) was conducted to derive a composite measure. Two factors were generated, broad parental involvement and specific parental involvement. Mixed-effects logistic regression was run using physical activity as the dependent variable and the two composite measures of parental involvement as predictors. The same mixed-effects logistic regression was performed using screen time as the dependent variable. Results: Both measures of parental involvement showed a statistically significant positive relationship with physical activity. Both measures of parental involvement were significantly associated with screen time. Conclusion: Results suggest that specific parental involvement leads to an increase in weekly physical activity and a decrease in daily screen time. Increasing physical activity and reducing screen time have demonstrated clear reductions in the rate of obesity amongst children. To improve healthy behavior and reduce the likelihood of childhood obesity, parents should be directly involved in their child's school behavior.